Metropolitan area of Rome: an integrated vegetation study by remote sensing and field data - Giannini, M; Anselmi, S; Melini, S; Allegrini, A; Manes, F (Remote Sensing and Data Fusion over Urban Areas, IEEE/ISPRS Joint Workshop 2001, 2001)
The objective of this work is to assess the impact of environmental stresses, both natural (water stress, due to summer dryness typical of the Mediterranean climate) and anthropogenic (atmospheric pollution), on the vegetation in sites of great naturalistic value and under strong anthropic pressure in the Rome metropolitan area. The species <e1>Q</e1>uercus ilex L<e1>.</e1> (holm oak), an evergreen oak, has been studied through ecophysiological measurements performed in the field and Landsat TM images relating to the Rome metropolitan area. The results obtained show a greater degree of structural and functional alteration in individual holm oaks within the urban area compared with those in the protected areas outside of the central zone. In particular, in 1993 the main stress factor for vegetation is attributable to climatic conditions, whereas in 1998 ozone atmospheric concentration caused an evident alteration of the parameters studied
Keywords: Environmental stresses; metropolitan area; multiscale approach; Vegetation